Improving Creative Thinking Skills of Early Childhood by Utilizing Robotic Activities in Learning Process - Miftahus Surur; Muhammad Ridhwan; Achmad Abdul Azis; Irma Noervadila; Ruski (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2023)
This study aims to determine the effect of robotics activities on improving the creative thinking skills of early childhood. This study used quanitative research with the Single Subject Design (SSD) method. The research design used in this study is using the A-B-A reversal design. Data collection was carried out using with a pre-test post-test experimental research design without clear control. The results of this study indicate that robotics activities can improve the creative thinking skills of early childhood. Robotics activities can improve creative thinking skills because the implementation of robotics activities is an activity based on constructive and manipulative activities. The characteristics of creative thinking skills that are improved through robotic activities are fluency, flexibility, originality, elaboration, and tenacity and patience. The relationship between robotics activities and creative thinking skills is that robotics activities are designed to follow environmental developments. So that it can bring out creativity in humans in developing ideas and become a means of realizing these creative ideas.